2016
DOI: 10.1002/ece3.2130
|View full text |Cite
|
Sign up to set email alerts
|

The relative importance of reproduction and survival for the conservation of two dolphin populations

Abstract: It has been proposed that in slow‐growing vertebrate populations survival generally has a greater influence on population growth than reproduction. Despite many studies cautioning against such generalizations for conservation, wildlife management for slow‐growing populations still often focuses on perturbing survival without careful evaluation as to whether those changes are likely or feasible. Here, we evaluate the relative importance of reproduction and survival for the conservation of two bottlenose dolphin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
140
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(149 citation statements)
references
References 65 publications
9
140
0
Order By: Relevance
“…The 3.4% rate is also well above growth rates that have been observed or modeled for other Tursiops truncatus populations, i.e. 1.8 and 0.5% for Sarasota Bay, and Shark Bay, Australia, respectively (Manlik et al 2016, R. S. Wells unpubl. data), and well above the growth rates estimated from our Bayesian framework using age-at-death data for the 4 baseline BSE sites (range 1.1 to 2.8%).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The 3.4% rate is also well above growth rates that have been observed or modeled for other Tursiops truncatus populations, i.e. 1.8 and 0.5% for Sarasota Bay, and Shark Bay, Australia, respectively (Manlik et al 2016, R. S. Wells unpubl. data), and well above the growth rates estimated from our Bayesian framework using age-at-death data for the 4 baseline BSE sites (range 1.1 to 2.8%).…”
Section: Discussionsupporting
confidence: 76%
“…increased reproduction or in creased survival), resulting in an accelerated growth rate that will then slow as the population increases. Elasticity analyses of matrix population models in odontocetes have suggested that non-calf survival could have the greatest influence on population growth (Brault & Caswell 1993), yet field studies have shown variability in reproductive rates over time and across stocks or pods, while non-calf survival rates remain relatively constant (Wells & Scott 1990, Brault & Caswell 1993, Manlik et al 2016. Other empirical data provide evidence for DD growth in at least 9 species of cetaceans: 8 of these showed evidence of DD birth rate, 5 showed evidence of DD age at first reproduction, and only 1 (Orcinus orca) showed evidence for DD juvenile or adult survival (Fowler 1984).…”
Section: Introductionmentioning
confidence: 99%
“…The 116 completed questionnaires are analysed using 95% confidence intervals of proportions (reported as percentages) and Pearson' chi-square test for categorical data (Howell 2010) to investigate whether place of residence and/or DDC visitation influences visitor attitudes towards the feeding of wild dolphins and the tourism benefits of dolphin feeding. Numeric values appear as the Value ± 95% Confidence Interval, which is likely to contain the mean response of the broader visitor population.…”
Section: Discussionmentioning
confidence: 99%
“…The resident wild dolphin population of Koombana Bay is a major tourism drawcard for the regional city of Bunbury focused around the iconic Dolphin Discovery Centre tourist attraction (Bunbury Visitors Centre, 2016;Bunbury Geographe Tourist Strategy, 2015); Manlik et al, 2016 38′59.60″E), provides regulated beach based dolphin interactions; eco cruises; and dolphin swim tours, which all provide tourists with up-close dolphin encounters (DDC, 2015a). There is no feeding associated with the DDC eco cruises or the dolphin swim tours, but the DDC does provide minimalistic strictly controlled reward feeding as described above for the beach based dolphin interactions (DDC, 2015b).…”
Section: Koombana Bay Wild Dolphin Populationmentioning
confidence: 99%
“…The resident wild population of Indio-Pacific Bottlenose Dolphins ( Tursiops aduncus ) at Koombana Bay in the regional city of Bunbury, Western Australia and the local Dolphin Discovery Centre (DDC) are important drawcards for this marine tourism destination [2], [3], [4]. While visitors can experience the dolphins in regulated encounters coordinated by the DDC, anecdotal evidence suggests that people use private boats to seek out and interact with these wild dolphins on their own terms, which may have a negative impact on the resident dolphin population [1], [5].…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%